Sistem Pesanan Produk Kecantikan dan Kesihatan Untuk Kedai Kalz Agency: Beauty and Health Product Ordering System for Kalz Agency Stores - Mohamad Madon, Mizani; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2022)
The Beauty and Health Product Ordering System for Kalz Agency Stores is a web-based system that makes it easy for customers to order products and get suitable product recommendations without having to be present on the premises. The main problem faced by Kalz Agency Stores is that there is still no system to recommend products, information on products is not easily available and any orders and inquiries about products require customers to physically interact with the seller at the business premises. Next, the main objective of this project is to identify the needs required by the employees of Kalz Agency Stores in the procedure of giving product recommendations and managing customer orders. Prototype System Methodology was chosen to develop this system because prototype can help developers to understand the needs of users easily. Any feedback from users will be analysed, designed and re-implemented to address deficiencies and improve the proposed features. This process is done until the user is satisfied with the prototype produced. The model also helps the customer to realize any necessary modifications before the final implementation is done in the system. The system was developed using Visual Studio Community 2019 software using C# programming language and Microsoft SQL Server Management Studio 18 database. The result of this project is that Kalz Agency Stores can manage data records of product information sold, data records of customers who have dealt with them, manage orders and able to promote products more systematically. From the customer’s perspective, customer will easily obtain product information, receive product recommendations and place orders outside the operating hours of the premises. Therefore, the system developed will be able to facilitate transactions between sellers and customers of Kalz Agency Stores.